MODEL ASSESSMENT OF SCIENTIFIC LITERACY BASED ON OBSERVATION OF CHILDREN AGED 5-6 YEARS: DEVELOPMENT STUDY - Rivo Panji Yudha; Siti Aisyah (Adisam Publisher, 2026)
This research aims to determine the development of an observation-based science literacy assessment model for early childhood in Padang Panjang Village, to assess the feasibility of the observation-based science literacy assessment model for early childhood in Padang Panjang Village as valid and reliable, and to evaluate the science literacy skills of children before and after using the observation-based science literacy assessment model. This research is conducted in all kindergartens in Padang Panjang Village, Tanta District, Tabalong Regency, South Kalimantan Province. This research is a type of research and development. The research and development model applied is the 4D (Four-D) development model, which includes the stages of definition research, design, and development. The research results indicate that 1) the initial stage of the study reveals a substantial gap in the practice of science literacy assessment at the early childhood education level. As many as 70% of teachers acknowledge that they do not possess systematic assessment instruments, indicating methodological weaknesses in measuring children's science abilities. 2) the feasibility of the assessment model instruments: These assessment instruments are deemed suitable for use, with a very high validity level (86.02%) and strong reliability (average ICC value of 0.84).